Rainfall and microbial contamination in Alberta well water. Issue 1 (June 2016) - Valeo, Caterina; Checkley, Sylvia; He, Jianxun; Neumann, Norman
Abstract : Spatial and seasonal patterns in the positive rates of total coliforms and Escherichia coli in Alberta well water were investigated to gain insight into well water microbial contamination. Analysis was conducted in the presence of total coliforms (77  135 tests) and E. coli (77  132 tests) in well water from 2004 to 2009 along with monthly estimates of precipitation, all of which were aggregated to 13 zones across Alberta by using Voronoi tessellation. Regression combined with autocorrelation analysis was employed to develop wave functions for data assembled in each zone. Precipitation was found to peak in June or July in all 13 regions. The positive E. coli rate was found to peak in June, July or August, but the positive total coliform rate peaked in August, September or October. Spatial statistical analysis revealed a potential association of total coliforms and E. coli with precipitation in two heavily populated basins. Spatial density analysis revealed a cluster of positive tests of total coliforms and E. coli in a narrow spatial extent in June and July of 2005.